Malignant hemangiosarcoma in a renal allograft: diagnostic difficulties and clinical course after nephrectomy and immunostimulation. (12th April 2014) - Kuntzen, Daniela; Tufail Hanel, Majida; Kuntzen, Thomas; Yurtsever, Hüseyin; Tuma, Jan; Hopfer, Helmut; Springer, Oliver; Bock, Andreas
Summary Hemangiosarcomas are rare tumors of endothelial cell origin. To date, only 20 cases of hemangiosarcoma have been described after renal transplantation, occurring mostly in the skin or in a dialysis fistula. We report a primary metastasizing hemangiosarcoma arising from a renal allograft. The patient was treated with transplant nephrectomy, discontinuation of immunosuppression, and immunostimulation with pegylated interferon‐α‐2a and has now been in complete remission for 3 years.